Applications of Computing, Automation and Wireless Systems in Electrical Engineering Proceedings of MARC 2018 - Mishra, Sukumar; Sood, Yog Raj; Tomar, Anuradha (Lecture Notes in Electrical Engineering, 2019)
This book discusses key concepts, challenges and potential solutions in connection with established and emerging topics in advanced computing, renewable energy and network communications. Gathering edited papers presented at MARC 2018 on July 19, 2018, it will help researchers pursue and promote advanced research in the fields of electrical engineering, communication, computing and manufacturing.